Initiation of air ionization by ultrashort laser pulses: evidence for a role of metastable-state air molecules. (1st June 2018) - Bulgakov, A V; Mirza, I; Bulgakova, N M; Zhukov, V P; Machulka, R; Haderka, O; Campbell, E E B; Mocek, T
Abstract: Transmission measurements for femtosecond laser pulses focused in air with spectral analysis of emission from the focal region have been carried out for various pulse energies and air pressures. The air breakdown threshold and pulse attenuation due to plasma absorption are evaluated and compared with calculations based on the multiphoton ionization model. The plasma absorption is found to depend on the pulse repetition rate and is considerably stronger at 1 kHz than at 1–10 Hz. This suggests that accumulation of metastable states of air molecules plays an important role in initiation of air breakdown, enhancing the ionization efficiency at high repetition rates. Possible channels of metastable-state-assisted air ionization and the role of the observed accumulation effect in laser material processing are discussed.